Mist net effectiveness to determine bird richness in a montane forest of Central Andes (Salento, Quindío, Colombia) (Revista de Investigaciones Universidad del Quindío, 2015)
Mist nets have been used to conduct bird inventories in several Neotropical habitats, but rarely their effectiveness have been evaluated in comparison to count points. This study compares the effectiveness of the mist nets and count points in determining the diversity of montane forest birds in montane forest of the Colombian Central Andes. During 6 months, we used mist nets in different habitats with a capture effort of 2630 net-hours. 608 individuals of 81 species of birds were recorded. In the point counts 106 species of birds were detected. However we captured 31 species that were not recorded in the count points. Higher capture rate occurred during the early hours of the morning and at noon (06:00-09:00 h and 12:00-13:00 h) while in the afternoon the catch rate declined. From our data and the comparison with the data of other authors, we conclude that point counts are useful to obtain a representative bird inventory in less time than using mist nets alone. However, the role of mist nets in inventories must be considered as complementary. And they are necessary to obtain other information such as morphological measurements reproduction clues and molt.
Keywords: bird richness; captures; effectiveness; montane forest; point counts